2011
DOI: 10.1016/j.vetimm.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant interferon omega in feline retrovirosis: From theory to practice

Abstract: Type-I interferons (IFNs) are cytokines that have non-specific antiviral activity, participating mostly in innate defense mechanisms. Their administration has been proposed to treat several viral and immunomediated diseases as an immunomodulatory therapy. Due to its availability, recombinant human interferon-alpha (rHuIFN-α) has been studied in relation to feline retrovirosis, both in vitro and in vivo. However, IFNs are species-specific and antibodies have been shown to develop in response to the high rHuIFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 33 publications
7
64
1
3
Order By: Relevance
“…This activity indicates that cells have a tendency to be insensitive to IFN-ω from distantly related species [23]. IFN-ω is involved in the nonspecific response based on increased expression of several acute phase proteins and MHC I molecules; upregulation of the phagocytic activities of whole blood cells, macrophages and NK cell activities; and decreased concurrent viral excretion [71-74]. Different therapy protocols might also contribute to the distinct expression of innate immunity cytokines following IFN-ω treatment.…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity indicates that cells have a tendency to be insensitive to IFN-ω from distantly related species [23]. IFN-ω is involved in the nonspecific response based on increased expression of several acute phase proteins and MHC I molecules; upregulation of the phagocytic activities of whole blood cells, macrophages and NK cell activities; and decreased concurrent viral excretion [71-74]. Different therapy protocols might also contribute to the distinct expression of innate immunity cytokines following IFN-ω treatment.…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
“…The first study supporting its clinical application was conducted in 2004 and found that cats infected with FeLV or co-infected FIV displayed a significant clinical improvement and a prolonged survival with rFeIFN-ω treatment [73, 116]. Other studies showed that treatment with rFeIFN-ω improved clinical signs, decreased concurrent viral excretion and hematologic parameters, and increased levels of acute phase proteins, a key component of the innate immune system [71, 119]. However, rFeIFN-ω did not change hypergammaglobulinemia, proviral load, or viremia.…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%
“…Increasing evidence suggests that IFN-ω may be associated with the nonspecific immune response based on increased survival time, the presence of acute-phase proteins (serum amyloid-A, α-1-glycoprotein, and the C-reactive protein), the phagocytic activities of whole blood cells and macrophages, natural killer cell activities, and reduced concurrent viral excretion [44][45][46][47][48]. In general, increasing the number of ISGs, Mx proteins, and ZAPS, which could enhance pathogen detection and innate immune signaling, indicates that IFN-ω elicits an immune response.…”
Section: Regulating the Innate Immune Responsementioning
confidence: 99%
“…AZT (3'-azido-2',3'-dideoxythymidine) is a nucleoside analogue (thymidine derivative) that blocks the retroviral reverse transcriptase and inhibits the replication of FIV in vivo and in vitro. As with HIV, FIV resistance may arise after 6 months of treatment Doménech et al, 2011;Mohammadi & Bienzle, 2012).…”
Section: Diagnosis and Management Of Fiv-infected Catsmentioning
confidence: 99%